2015
DOI: 10.5897/ajar2015.9487
|View full text |Cite
|
Sign up to set email alerts
|

Cellulases produced by the endophytic fungus Pycnoporus sanguineus (L.) Murrill

Abstract: Cellulases are enzymes that act on the hydrolysis of cellulosic substrates and comprise a complex capable of hydrolyzing cellulose and producing glucose. This conversion can be performed by an enzymatic complex found in secretions of such microorganisms as fungi and bacteria. The challenge is to transform this conversion into a quicker and more cost-effective process. The objective of this study was to evaluate the activity of the cellulase produced by the fungus Pycnoporus sanguineus (L.) Murrill, strains D1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Cellulases are widely used in different industries like animal feed, agriculture, laundry and detergent, textile, paper and pulp, brewing, food processing, olive oil extraction, and biofuel production. Cellulase is recorded to be produced by the endophytic isolates Penicillium oxalicum from Taxus cuspidate (Li et al, 2021) and Pycnoporus sanguineus from Baccharis dracunculifolia (Onofre et al, 2015).Laccase is an important enzyme as it can oxidize both toxic and nontoxic substrates and is utilized in the textile industry, food processing industry, wood processing industry, pharmaceutical industry, and chemical industry. Previous studies reported that laccase production by endophytic fungi, Monotospora sp.…”
Section: Discussionmentioning
confidence: 99%
“…Cellulases are widely used in different industries like animal feed, agriculture, laundry and detergent, textile, paper and pulp, brewing, food processing, olive oil extraction, and biofuel production. Cellulase is recorded to be produced by the endophytic isolates Penicillium oxalicum from Taxus cuspidate (Li et al, 2021) and Pycnoporus sanguineus from Baccharis dracunculifolia (Onofre et al, 2015).Laccase is an important enzyme as it can oxidize both toxic and nontoxic substrates and is utilized in the textile industry, food processing industry, wood processing industry, pharmaceutical industry, and chemical industry. Previous studies reported that laccase production by endophytic fungi, Monotospora sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the higher cost, using a large amount of organic nitrogen source such as yeast extract was not the most efficient method for industrial enzyme production. Our research did not show the best result of endoglucanase production, however, it indicated the potential of polypore fungi M. xanthopus strain KA038 to produce better cellulolytic activity compared with other polypore fungi such as Melanoporia sp., Pycnoporus sanguineus , Pycnoporus coccineus and Coriolus versicolor (Montoya et al, 2015; Onofre et al, 2015; Chuwech et al, 2016; de Oliveira et al, 2016). Thus, this result demonstrated that M. xanthopus was a remarkable species of polypore fungi in producing endoglucanase activity.…”
Section: Discussionmentioning
confidence: 99%